Zoneamentos agroecológicos e seus reflexos no desenvolvimento da produção agrícola familiar municipal no estado do Pará: a questão da seguridade alimentar da população local - NASCIMENTO JÚNIOR, João de Deus Barbosa (Universidade Federal do Pará, 2011)
The Amazonian area represents a group of conflicts of interests now that they present as central axes to the ecological subject and the need of guaranteeing the survival of the local population. The present work discusses the efficiency, efficacy and effectiveness of part of the Zonings Ecological-Economics accomplished by the Brazilian Company of Agricultural Research - EMBRAPA, through his Unit Decentralized in Pará, Center of Research Agro-forest of the Amazonian Oriental Embrapa Amazônia Oriental, in the annuals from 1975, 1998, 1999, 2000, 2001, 2002, 2003 and 2004, when he assisted to dozens of requests, on the part of municipal managers of the State of Pará, with respect to the reflexes of his use or disuse, as planning instrument for the endogenous development of those municipal districts, mainly to those tied the warranty of the alimentary sureness of the population in them residents, of products as: Rice (Oriza sativa) and Bean (Phaseolus vulgaris L.), produced by small family producers, that according to Costa (1973), it is treated of the group formed by those farmers that use earth modules of up to two hundred hectares, and, that ninety five percent of the busy labor with the agricultural activities, is family. In that research, they will be appraised the ecologicaleconomical zonings of the municipal districts, belonging the small area of Paragominas: Abel Figueirêdo, Rondon do Pará, Paragominas and Bom Jesus do Tocantins. Of beforehand, knows - if what only the ZEE, no they render in totum, a panacea (remedy for everyone the evils), but treated - if from a tool potent about to delineate the use of the territory & from earth & she'd help quite when used about to definition from the area potentially promising about to production of foods basic.